Soil resource availability is much more important than soil resource heterogeneity in determining the species diversity and abundance of karst plant communities. Issue 23 (28th October 2021) - Liu, Yuan; Qi, Wenchao; He, Danni; Xiang, Yunrong; Liu, Jinchun; Huang, Huimin; Chen, Miao; Tao, Jianping
Abstract: Resource availability and heterogeneity are recognized as two essential environmental aspects to determine species diversity and community abundance. However, how soil resource availability and heterogeneity determine species diversity and community abundance in highly heterogeneous and most fragile karst landscapes is largely unknown. We examined the effects of soil resource availability and heterogeneity on plant community composition and quantified their relative contribution by variation partitioning. Then, a structural equation model (SEM) was used to further disentangle the multiple direct and indirect effects of soil resource availability on plant community composition. Species diversity was significantly influenced by the soil resource availability in shrubland and woodland but not by the heterogeneity in woodland. Abundance was significantly affected by both soil resource availability and heterogeneity, whereas variation partitioning results showed that soil resource availability explained the majority of the variance in abundance, and the contribution of soil resource heterogeneity was marginal. These results indicated that soil resource availability plays a more important role in determining karst plant community composition than soil resource heterogeneity. Our SEMs further found that the multiple direct and indirect processes of soil resource availability in determining karst species diversity and abundance were different in different vegetation types. Soil resource availability and heterogeneity both played a certain role in determining karst plant community composition, while the importance of soil resource availability far exceeded soil resource heterogeneity. We propose that steering community restoration and reconstruction should be highly dependent on soil resource availability, and multiple direct and indirect pathways of soil resource availability for structuring karst plant communities need to be taken into account. Abstract : Both limited resource availability and significant resource heterogeneity are key features of karst landscapes. Our study first considered simultaneously resource availability and heterogeneity in karst regions and then quantified and compared the effects of resource availability and heterogeneity on community abundance and species diversity from the relevance‐theoretic perspective. More importantly, our study has important guiding significance to the vegetation restoration.